2010
DOI: 10.1016/j.jvir.2010.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced Phenotypic Switch of Fibroblasts to Myofibroblasts through a Matrix Metalloproteinase 2/Tissue Inhibitor of Metalloproteinase–mediated Pathway: Implications for Venous Neointimal Hyperplasia in Hemodialysis Access

Abstract: Purpose Hemodialysis grafts fail because of venous neointimal hyperplasia formation caused by adventitial fibroblasts which have become myofibroblasts (α-smooth muscle actin positive cells) and migrate to the neointima. There is increased expression of hypoxia inducible factor-1 alpha (HIF-1α in venous neointimal hyperplasia formation in experimental animal model and clinical samples. We hypothesized that under hypoxic stimulus (HIF-1α fibroblasts will convert to myofibroblasts through a matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 48 publications
(51 reference statements)
1
57
0
Order By: Relevance
“…In particularly, a significant increase in active MMP-2, TIMP-1 and TIMP-2 production was also observed under hypoxic stimulus when compared to normoxic fibroblasts [44]. It has been shown that the reactive oxygen species (ROS)-induced oxidative stress increases MMP activity and potentially modulates fibroblast proliferation and collagen synthesis [49].…”
Section: Expression and Regulation Of Mmps In Vasculature Vascular Cellsmentioning
confidence: 97%
See 2 more Smart Citations
“…In particularly, a significant increase in active MMP-2, TIMP-1 and TIMP-2 production was also observed under hypoxic stimulus when compared to normoxic fibroblasts [44]. It has been shown that the reactive oxygen species (ROS)-induced oxidative stress increases MMP activity and potentially modulates fibroblast proliferation and collagen synthesis [49].…”
Section: Expression and Regulation Of Mmps In Vasculature Vascular Cellsmentioning
confidence: 97%
“…Different cell types that constitute the cellular component of the vasculature, including endothelium, SMCs, fibroblasts and infiltrating innate immune cells which infiltrate the vessel wall, are described as the major cellular sources of MMPs in adult vasculature [41][42][43][44] (table S1). The diverse functions of MMPs in vasculature mainly depend on its expression and activity.…”
Section: Expression and Regulation Of Mmps In Vasculature Vascular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is evidence that cultured murine fibroblasts exposed to hypoxia can change their phenotype to myofibroblasts [13]. Although such cells produce collagen, it is the contractile ability of a-smooth muscle actin which may be of particular relevance as myofibroblasts are known to produce scar contracture [5].…”
mentioning
confidence: 99%
“…Hypoxia has been shown to stimulate collagen synthesis by cultured human vascular-derived myofibroblasts [24]. In contrast, the effects on matrix metalloproteinases have been mixed: several studies reported increases in MMP-2 synthesis in cultured rodent fibroblasts [1,13], whereas exposure of cultured human myofibroblasts to chronic hypoxia attenuated MMP-2 activation [20]. The overall effect of hypoxia on collagen deposition is, however, best assessed in the intact heart.…”
mentioning
confidence: 99%